Resection for bronchial carcinoma in the elderly - Evans, E. W. Thompson (1973)
The results of surgery for carcinoma of the bronchus among an elderly population are reviewed in relation to the total number of cases seen. Although there is a 20% operative hospital mortality, nevertheless a survival rate of 39% for four years makes surgery in the elderly worthwhile. The span of life in untreated cases is even less than in the younger age groups.